A novel fuel injected mass feedback-control for single and multiple injections in direct injection systems for CI engines. (15th February 2023) - Ferrari, Alessandro; Novara, Carlo; Vento, Oscar; Violante, Massimo; Zhang, Tantan
Highlights: A novel feedback-control strategy for the injected quantity is built up. A rapid prototyping hardware is used to test the developed control. Single and multiple injection performance of the prototypal hardware is analyzed. Abstract: A new feedback-control capable to enhance the fuel injected quantity accuracy has been proposed and tested. The experimental pressure in the rail and that measured along the rail-to-injector pipe, in the vicinity of the injector inlet, have been used as input data to a home-made hydraulic model. By means of this model the pressure downstream of the gauged orifice at the interface between the rail and the rail-to-injector pipe is determined; the mass at the injector inlet can be obtained by means of an integration of the estimated flow-rate entering the injector. A robust mathematical law can be established between the mass that enters the injector and the one injected, thus, a feedback-control based on the error between the target injected quantity stored in the ECU and the predicted injected mass has been designed and implemented for the ET correction. The new feedback-strategy has been applied to control both single and double (pilot-main) injection schedules by using a rapid prototyping hardware. Regarding single shots, the new control results to be capable of reducing the injected mass inaccuracy, which is due to the different thermal regimes experienced by the injector, below 0.6 mg (the standard open loop control can feature an error up to 2 mg when the fuel tank temperature is varied), while for the pilot-main schedules it is possible to dramatically reduce the inaccuracy on the desired overall injected quantity (below 1 mg) when digital or continuous rate shaping strategies are implemented.